Cyanide degradation by pseudomonas pseudoalcaligenes strain W2 Isolated from mining effluent - Belinda Tiong,; Zaratulnur Mohd Bahari,; Nor Sahslin Irwan Shah Lee,; Jafariah Jaafar,; Zaharah Ibrahim,; Shafinaz Shahir, (Universiti Kebangsaan Malaysia, 2015)
Cyanide is highly toxic to the living organisms as it inhibits respiration system in the cell mitochondria. Cyanide is commonly used in gold extraction process and its discharge into the environment not only causes pollution but it also brings harm to the surrounding population. Chemical treatment is expensive and the use of hazardous compound can exacerbate the problem. Biodegradation offers cheap and safe alternative as it overcomes the problems faced by chemical treatment. In this study, indigenous bacteria from mining wastewater were isolated. Cyanide degradation was done via shake flask method. A bacterium, designated W2 was found able to grow in the mining wastewater. 16S rRNA analysis identified the strain as Pseudomonas pseudoalcaligenes which could tolerate up to 39 mg/L cyanide concentration and growth was depleted at 52 mg/L. 60% cyanide degradation was achieved in wastewater containing medium. End-product analysis from high performance liquid chromatography (HPLC) detected formamide implicating the role of cyanide hydratase in cyanide degradation. It can be concluded that P. pseudoalcaligenes is capable of biodegrading cyanide and its potential in wastewater treatment containing cyanide is feasible.